2022
DOI: 10.21203/rs.3.rs-1817471/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simplistic approach to the study of two-point correlation function in galaxy clusters

Abstract: We developed the functional form of the two-point correlation function under the approximation of fixed particle number density ¯n. We solved the quasi-linear partial differential equation (PDE) through the method of characteristics to obtain the parametric solution for the canonical ensemble. We attempted many functional forms and concluded that the functional form should be such that the two-point correlation function should go to zero as the value of system temperature increases or the separation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We can employ statistical methods to find the statistical distribution of matter at largest possible scales [8]. Recently there has been a lot of progress on the study of the effect of modified gravity laws on the clustering of galaxies using statistical mechanics [9][10][11][12][13][14][15][16][17][18][19][20]. The effect of the modifications incorporated has been anticipated in the strength of the clustering parameter b.…”
Section: Introductionmentioning
confidence: 99%
“…We can employ statistical methods to find the statistical distribution of matter at largest possible scales [8]. Recently there has been a lot of progress on the study of the effect of modified gravity laws on the clustering of galaxies using statistical mechanics [9][10][11][12][13][14][15][16][17][18][19][20]. The effect of the modifications incorporated has been anticipated in the strength of the clustering parameter b.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical method can be emplyed to study the mass distribution on the largest possible scale [9]. In recent past there has been a tremendous effort to study the effect of modified gravity theories on the galaxy clustering through statistical and thermodynamic methods [10][11][12][13][14][15][16][17][18][19][20][21][22]. It has been observed that the modified theories of gravity does affect the clustering process through a change in a parameter that is related to the strength of correlation called clustering parameter, originally defined as the ratio of Kinetic to potential energy, b = K/2W .…”
Section: Introductionmentioning
confidence: 99%